The cysticercosis in muscles is one of the causes of lumps in human - Rai, B K; Shashikar, Dr. (Health Renaissance, 2012)
Introduction: Cysticercosis is commonly encountered in this part of the world. It can manifest in many different form. Objective: To report a case of cysticercosis which presented with a lump in axilla. Case: A 36 year old man from Dharan presented with the chief complaint of lump in the right axilla for 9 months and two lumps in left axilla for 3 months. The onset of lump was insidious and gradually progressive in nature. The examination revealed a single mass in the medial surface of right upper arm, approximately 3x3cm in size, not fixed with the skin, slightly movable and mildly tender and another two masses around 1x2 cm in left axilla with similar characteristics as the right one. The ultrasonography showed heterogenous lesion measuring 27mm x 18 mm in medial aspect of right upper arm and two similar lesions measuring 14.5 x11mm and 11 x 10 mm in left axilla suggesting "Cysticercosis". The lumps were surgically removed successfully. Conclusion: Cysticercosis is one of the causes of lump in axillay region. It can be diagnosed ultrasonographically and treated by surgical removal. DOI: http://dx.doi.org/10.3126/hren.v10i2.6591 Health Renaissance 2012; Vol 10 (No.2); 160-161